A Review of the Management, Outcomes, and Barriers to Rehabilitation in Patients With Post-intensive Care Syndrome - Arnengsih Nazir; Lynna Lidyana; Shofiyyah Sayyidah (Iranian Rehabilitation Journal)
Objectives: Post-intensive care syndrome (PICS) is a multidimensional problem comprising physical, cognitive, and psychological symptoms experienced by patients during and after intensive care. Symptoms can persist for years and impact patients and their families. Rehabilitation programs were recognized as a preventive and management strategy for PICS; however, several obstacles to their implementation exist. Therefore, this study aimed to determine the interventions, outcomes, and barriers to rehabilitation in patients with PICS. Methods: A review study was conducted from November 2020 to January 2021 by analyzing articles selected from Google Scholar and PubMed databases. Results: Twenty-two studies were eligible for inclusion. Rehabilitation interventions for patients with PICS were performed through the ABCDE bundle, which consistes of A, airway management, assessment, prevention, and management of pain; B, breathing trials, including daily interruptions of mechanical ventilation, spontaneous awakening trials, and spontaneous breathing trials; C, choice of analgesia and sedation, coordination of care, and communication; D, delirium assessment, prevention, and management; and E (ABCDE), early mobility and exercise, physical therapy, early mobilization, cognitive and psychological approaches, intensive care unit (ICU) diary, education, consultation, and follow-up management. The outcomes included improvements in physical and cognitive function anddecreased psychological symptoms. Barriers to rehabilitation were patient-related, structural, and cultural. Discussion: Rehabilitation interventions for patients with PICS employ a multidimensional approach, demonstrating positive impacts on physical, cognitive, and psychological function. However, the presence of barriers hinderes adequate management.